Bicycle sharing station planning: From free-floating to geo-fencing. (February 2023) - Cai, Yutong; Ong, Ghim Ping; Meng, Qiang
Highlights: This study proposes a novel data-driven bike sharing station planning problem to transform free-floating bike sharing systems into geo-fencing ones. This study incorporates multiple objectives in the planning for the stations of bike sharing systems. This study formulates the proposed problem into a multi-objective integer non-linear programming model and an equivalent linearized integer model. . This study further designs a tailored simulation-based heuristics for tackling large-scale problems. Abstract: Bicycle sharing systems (BSSs) are expanding with unparalleled speed all over the world due to various advantages of cycling such as cost effectiveness, environmentally friendliness, capability to bridge other public transport modes and reduce private vehicle usage. One of the latest trend of BSS mode appears to be free-floating, which offers more flexibility in bike rental and return for cyclists in terms of service locations. However, despite the convenience brought by the free-floating BSS to the users, it also causes a headache for the authorities, largely attributed to its poor enforcement on regulating bad user behaviours, which significantly deteriorates the city scape. In order to preserve the benefits of BSSs and meanwhile solve the problems caused by free-floating BSS, this study develops a multi-objective integer non-linear programming (MOINLP) model to convert an existing free-floating BSS into a geo-fence-based one by determining the geo-fencing stations to be opened, their corresponding parking capacities and deployment of bikes. The three objectives of the developed MOINLP model are minimizing monetary cost, user dissatisfaction as well additional first-/last-mile walking distance of users. The MOINLP model is transformed into an equivalent multi-objective integer linear programming (MOILP) model. The augmented ε -constraint method (AUGMECON2) is customized to solve the MOILP model for exact Pareto optimal solutions while a tailored simulation-based heuristic method is proposed to solve large-scale problems. The numerical experiments have testified the good performance of our proposed solution method and we extend our analysis to Beijing BSS to gain planning insights and policy implications.